Proper configuration of metallic energy dissipation system in shear-type building structures subject to seismic excitation - Li, Zongjing; Shu, Ganping; Huang, Zhen (Journal of constructional steel research, 2019)
Passive control using metallic energy dissipation system has been proved to be a reliable means of seismic upgrading for building structures. Furthermore, configuration of the metallic energy dissipation system within a structure may have significant influence on the overall seismic performance. This paper presents a systematic approach for optimal configuration of the metallic energy dissipation system in shear-type building structures subject to seismic excitation consistent with the design code, where the mechanical parameters of the metallic energy dissipation component in each story level are taken as the optimization variables. Two objective functions as well as two optimization levels are proposed. An improved real-coded genetic algorithm is employed as the optimizer. The framework of the optimal configuration design process is given and demonstrated in an application example. Based on the results of the application example, the influence of different algorithms, optimization levels and objective functions are further analyzed. Moreover, a simplified fine level optimization approach is proposed based on the parameter sensitivity, which can yield satisfying results with less time. •The mechanical parameters of the MED component in each story level are taken as the optimization variables.•An improved real-coded genetic algorithm is proposed for solving the optimization problem.•The spectrally-adjusted earthquake ground motion is employed to conduct the nonlinear time history analysis.•A simplified fine level optimization approach is proposed based on the parameter sensitivity for better efficiency•A systematic design framework is proposed to properly configure the supplemental metallic energy dissipation system.